Probiotics for cognitive resilience: resetting the gut and recharging the mind / Kalavaty Ramasamy, Siong Meng Lim and Abu Bakar Abdul Majeed - Ramasamy, Kalavaty; Siong, Meng Lim; Abdul Majeed, Abu Bakar (Faculty of Pharmacy, 2024)
Longer life expectancy has seen many ageing nations, including Malaysia, in the face of the inevitable increased burden of late-life diseases (especially deterioration of cognitive function) that will have a huge impact on our society. It is increasingly recognised that ageing increases the likelihood of a frail gut with presentations of low-grade chronic inflammation (i.e., inflammaging), impaired immune response (i.e., immunosenescence) and reduced gut microbiota diversity (i.e, dysbiosis). Our findings from the AGELESS cohort and systematic review indicated increased pathobionts and reduced protective bacteria in the gut of the older adults (Rashidah et al., 2022). We have also identified faecal calprotectin as a potential intestinal inflammatory marker in older adults (Ahmad Fadzuli et al., 2024).